Characteristics of solar radiation at Xiaotang, in the northern marginal zone of the Taklimakan Desert - Lili Jin (PeerJ Inc., 2021)
The characteristics of solar radiation and the influence of sand and dust on solar radiation in the northern margin of Taklimakan Desert were analyzed using radiation observation data from 2018. The results showed that the annual total radiation, direct radiation, and scattered radiation at Xiaotang were 5,781.8, 2,337.9, and 3,323.8 MJ m−2, respectively. The maximum monthly total radiation, direct radiation, and scattered radiation were observed in July (679.8 MJ m−2), August (317.3 MJ m−2), and May (455.7 MJ m−2), respectively. The aerosol optical depth corresponded well with the scattered radiation, and the maximum value was in May. Further analysis showed a significant correlation between the total radiation and solar height angle under different weather conditions. Under the same solar height angle, total radiation was higher during clear days but lower on sandstorm days. Calculation of atmospheric transmittance showed that the average atmospheric transmittance on a clear day was 0.67; on sand-and-dust days, it was 0.46. When the atmospheric transmittance was 0.5, the increase in scattering radiation by aerosol in the air began to decrease. Probability analysis of radiation indicated the following probabilities of total radiation <500 W m−2 occurring on clear, floating-dust, blowing-sand, and sandstorm days: 67.1%, 76.3%, 76.1%, and 91.8%, respectively. Dust had the greatest influence on direct radiation; the probabilities of direct radiation <200 W m−2occurring on clear, floating-dust, blowing-sand, and sandstorm days were 44.5%, 93.5%, 91.3%, and 100%, respectively, whereas those of scattered radiation <600 W m−2were 100%, 99.1%, 98.1%, and 100%, respectively. Therefore, the presence of dust in the air will reduce scattered radiation.